2014
DOI: 10.1121/1.4883360
|View full text |Cite
|
Sign up to set email alerts
|

Compressive beamforming

Abstract: Sound source localization with sensor arrays involves the estimation of the direction-of-arrival (DOA) from a limited number of observations. Compressive sensing (CS) solves such underdetermined problems achieving sparsity, thus improved resolution, and can be solved efficiently with convex optimization. The DOA estimation problem is formulated in the CS framework and it is shown that CS has superior performance compared to traditional DOA estimation methods especially under challenging scenarios such as coher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
182
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(195 citation statements)
references
References 46 publications
(49 reference statements)
1
182
0
12
Order By: Relevance
“…Let 's' be the transmitted signal such that s ϵ c N . The array steering vector at each of the sensor array due to the source i can be written as in [9]: …”
Section: Classical Beamforming Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Let 's' be the transmitted signal such that s ϵ c N . The array steering vector at each of the sensor array due to the source i can be written as in [9]: …”
Section: Classical Beamforming Approachesmentioning
confidence: 99%
“…The key idea of compressed sensing is to recover a sparse signal from very few non-adaptive, linear measurements by convex optimization. Performance of CS technique in DOA estimation under number of sources and noise conditions is presented by Malioutov et al [8] Robustness of CS in sound source localization using sensor arrays has been demonstrated in [9] with coherent arrivals and snapshot deficient case.…”
mentioning
confidence: 99%
“…In underwater acoustics, we can also mention the use of convex-relaxation based algorithms, such as the Least Absolute Shrinkage and Selection Operator (LASSO) [4] or the Simultaneous LASSO (SLASSO) when considering multiple measurements (snapshots) [7]. All these latter techniques offer a high resolution, but are intrinsically not designed to be robust to random environmental fluctuations such as internal waves or sound speed spatiotemporal dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve its power resolution, so-called "high-resolution" techniques have then been proposed, distinguishing by the a priori information they consider on the nature and/or the number of sources. Among them, we can mention the well-known Minimum Variance Distortionless Response (MVDR) beamformer [2], the MUltiple SIgnal Classification (MUSIC) beamformer [3] and, more recently, sparse techniques [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since sparse or compressible signals have a wide range of applications, CS has been applied in many fields, such as radar and sonar [8][9][10], antenna beam forming [11,12], imaging [13,14], and video [15], to name a few. Nevertheless, there are still challenges, because CS reconstruction generally involves a heavy computational load and is time-consuming.…”
Section: Introductionmentioning
confidence: 99%